Peningkatan Keterampilan Membaca Pemahaman dengan Menggunakan Model Scramble di Kelas V SDN NO. 175/VI Ngaol Ilir - Susanti, Susi; Subhanadri, Subhanadri (CV. Master Literasi Indonesia, 2025)
This research was motivated by the low proficiency of students in the Indonesian language subject during the learning process, where teachers predominantly relied on lecture and question-and-answer methods. The study aimed to enhance the learning skills of fourth-grade students at SD 175/VI Ngaol Ilir through the implementation of the Scramble model. The Scramble model involves creatively arranging words or letters randomly to form answers or matching concepts related to the given questions. The research was designed as a classroom action research (CAR) study with the objective of determining whether the Scramble model could improve students' skills. Conducted over two cycles, the research utilized instruments such as teacher observation sheets, reading skill observation sheets, and achievement tests. The results indicated that applying the Scramble model significantly improved students' reading comprehension. This was evidenced by the increase in average reading comprehension scores from the final tests, with the first cycle achieving a completeness rate of 51.11%, which rose to 76.67% in the second cycle—a 25.56% improvement. Thus, it can be concluded that the Scramble model effectively enhances students' reading comprehension skills